Neo-Kantian Question on Method, the Problem of Form and the Meaning of Variability in Gustav Shpet and Ernst Cassirer’s Philosophy - Nikolai B. Afanasov (Кантовский сборник)
The Kantian legacy has had a key impact on the landscape of theoretical philosophy in the first half of the twentieth century. Philosophers both in Germany and in Russia saw Immanuel Kant’s ideas as seminal for their philosophical research. The main schools of that era were formed in discussions of the problems and the solutions which were proposed by Kant. The methodological legacy of the critical philosophy effectively became the main benchmark of the thinking of a whole generation of intellectuals. Research into the unity of “form” in the structure of human cognition was also in many ways mediated by the Kantian tradition. To prove this thesis I first look at the philosophy of Gustav Shpet who creatively interpreted the German tradition and proposed an original project of his own, and then I examine the theory of Ernst Cassirer, an outstanding representative of Neo-Kantianism who in the later period of his work proposed considering the phenomena of the humanities to be symbolic forms closest to the spontaneity of the biological. The common feature of the approaches of the two philosophers is their attempt to preserve the integrity of cognition which is destroyed by mathematisation of the common denominator (ultimate categorisation) and hierarchisation of the phenomena of human life. The alternative is the metaphor of mutational change, through which the concept of “form” acquires a new meaning. In conclusion I show that the analysis of the projects of Shpet and Cassirer has heuristic value for the historical-philosophical understanding of the fate of the Kantian philosophy and for modern philosophical culture.